Efficacy and tolerance of acne treatment using both spironolactone and a combined contraceptive containing drospirenone - Krunic, Aleksandar; Ciurea, Ana; Scheman, Andrew (Journal of the American Academy of Dermatology, 2008)
The use of either oral contraceptives or antiandrogens has been shown to be helpful in the treatment of women with acne. We investigated the safety and efficacy of acne treatment using both spironolactone and a combined contraceptive containing drospirenone. Twenty-seven women with either severe papular or nodulocystic facial acne were treated with a combined oral contraceptive containing 30 μg ethinyl estradiol and 3 mg drospirenone (EE/DRSP; Yasmin) and spironolactone (SL) 100 mg taken daily. A serum potassium level was obtained before initiation of therapy. Between 4 and 6 weeks after the start of both medications, a second serum potassium level was obtained. Side effects were recorded. No significant elevation of serum potassium was found in any of the subjects nor were there any reported additional side effects significant enough to discontinue treatment. At follow up, 85% of subjects were entirely clear of acne lesions or had excellent improvement, 7.4% were mildly improved, and 7.4% were not improved. This was a small prospective study. The combination of EE/DRSP and SL 100 mg daily appears to have efficacy and is well tolerated in the treatment of severe papular and nodulocystic acne in women.